2015
DOI: 10.1007/s13594-015-0219-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and lipolytic changes in high-pressure-treated raw milk cheeses during refrigerated storage

Abstract: High-pressure processing (HPP) has been used to control microorganisms and enzymes and avoid over-ripening in cheese. Excessive lipolysis is associated with over-ripening in cheese. However, little information about the effect of high pressure on microorganisms and lipolysis in mature cheese is available. For this reason, microbiological and lipolytic changes during refrigerated storage of pressurised Torta del Casar cheese (a raw ewe's milk cheese) were studied. Mature cheeses (60 days of ripening) were high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Most of the studies deal with fresh cheeses, or cheeses made from raw (unpasteurized) milk. For example, Rodríguez-Pinilla et al [ 32 ] studied the effect on microbiological and lipolytic changes during the refrigerated storage of pressurized (200 or 600 MPa for 5 or 20 min) Torta del Casar cheese (a raw ewe’s milk cheese). The results showed that the safety of the product was enhanced after HPP, while free fatty acid content was not significantly influenced by HPP [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies deal with fresh cheeses, or cheeses made from raw (unpasteurized) milk. For example, Rodríguez-Pinilla et al [ 32 ] studied the effect on microbiological and lipolytic changes during the refrigerated storage of pressurized (200 or 600 MPa for 5 or 20 min) Torta del Casar cheese (a raw ewe’s milk cheese). The results showed that the safety of the product was enhanced after HPP, while free fatty acid content was not significantly influenced by HPP [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rodríguez-Pinilla et al [ 32 ] studied the effect on microbiological and lipolytic changes during the refrigerated storage of pressurized (200 or 600 MPa for 5 or 20 min) Torta del Casar cheese (a raw ewe’s milk cheese). The results showed that the safety of the product was enhanced after HPP, while free fatty acid content was not significantly influenced by HPP [ 32 ]. The study of Stefanini and Vignalu [ 34 ] evaluated the shelf-life of a fresh Ricotta cheese after HPP (600 MPa for 3 min) stored in modified-atmosphere packaging (MAP), in comparison with cheeses stored in MAP without HPP treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highpressure processing (HPP) has been studied and applied as an alternative non-thermal process to conventional thermal pasteurization, with a 2-3-fold shelf-life extension for dairy Foods 2023, 12,1935 2 of 17 foods compared to the raw counterparts [4], and with low impact on quality. Several studies have revealed the advantage of HPP application at the optimum organoleptic ripening time of cheeses, ensuring the effective inactivation of microorganisms and thus improving safety [5,6]. For example, studies performed with Torta del Casar cheese [5,6] demonstrated that HPP treatment of 600 MPa/5 min at 60 days of ripening caused 2.3 and 2.5 log cycle reductions in Enterobacteriaceae and Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed the advantage of HPP application at the optimum organoleptic ripening time of cheeses, ensuring the effective inactivation of microorganisms and thus improving safety [5,6]. For example, studies performed with Torta del Casar cheese [5,6] demonstrated that HPP treatment of 600 MPa/5 min at 60 days of ripening caused 2.3 and 2.5 log cycle reductions in Enterobacteriaceae and Pseudomonas spp. viable cells numbers, respectively [5].…”
Section: Introductionmentioning
confidence: 99%